PENGARUH PEMAHAMAN BENDAHARA PENGELUARAN DAN PENGENDALIAN INTERNAL TERHADAP KETEPATAN PEMOTONGAN PAJAK DI LINGKUNGAN PEMERINTAH KABUPATEN TANAH DATAR - Annisa Maharani; Andria Ningsih (Ensiklopedia of Journal, 2026)
The accuracy of tax withholding by expenditure treasurers is an essential aspect of ensuring tax compliance and accountability in regional financial management. This study aims to examine the effect of expenditure treasurers' understanding and internal control on tax withholding accuracy in Regional Government Organizations of Tanah Datar Regency. A quantitative approach with a survey method was employed by distributing questionnaires to 41 expenditure treasurers selected through a saturated sampling (census) technique. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results indicate that expenditure treasurers' understanding has a positive and significant effect on tax withholding accuracy. Internal control also has a positive and significant effect on tax withholding accuracy. These findings imply that improving the competence of expenditure treasurers and strengthening the implementation of an effective internal control system can enhance tax withholding accuracy and support accountable regional financial governance.Keywords: Expenditure Treasurer Understanding, Internal Control, Tax Withholding Accuracy, SmartPLS, Local Government